2014
DOI: 10.1111/jhn.12259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of eating and drinking on body composition measurements by bioelectrical impedance

Abstract: Although there were statistically significant changes in body composition estimates after food or drink consumption, these were small and within the imprecision of the impedance technique, and so are unlikely to be of clinical significance. The present study suggests that impedance measures of body fatness in clinical settings do not require strict adherence to fasting, and this should increase the opportunities for clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 18 publications
4
45
0
1
Order By: Relevance
“…54 However, BIA may be inaccurate, owing to the occurrence of fluid imbalances consequent to an underlying inflammatory process in patients with cancer. 14 Indeed, as all individuals included in the studies analysed in this systematic review underwent a scan as part of their routine oncological care, CT scanning clearly offers a practical, precise and accessible method to identifying sarcopenia in large groups of patients with abdominal malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 However, BIA may be inaccurate, owing to the occurrence of fluid imbalances consequent to an underlying inflammatory process in patients with cancer. 14 Indeed, as all individuals included in the studies analysed in this systematic review underwent a scan as part of their routine oncological care, CT scanning clearly offers a practical, precise and accessible method to identifying sarcopenia in large groups of patients with abdominal malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, food diaries rely on patients to self-report; body mass index (BMI) assumes a typical distribution of fat and muscle tissues; and bioelectrical impedance analysis (BIA) relies on the patient to fast beforehand and for their internal fluid balances to be in equilibrium. 14 Differences also exist between single-frequency and multifrequency 1 impedance measurements. 15 Therefore, although the latter methods give an indication of nutritional status, 16 they may not have the specificity to accurately identify changes in muscle mass and strength, which has been shown to lead to negative outcome in disease trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Three of these studies reported increases in FM% after nutritional intake [ 14 , 24 , 25 ], which was different from our results. In contrast to our study, those previous studies used other BIA methods (segmental, multi frequency [ 14 ] and leg to leg [ 14 , 24 ]), had subjects remain in supine position for 12 h [ 25 ], included different time points for non-fasting measurements (20,40, and 60 min after eating) [ 14 ], or provided a higher energy intake (919 kcal [ 14 ], and 869 kcal [ 24 ]). Only two studies used wholebody SF BIA outcomes; one among healthy subjects [ 13 ] and one among elderly [ 26 ], and their results studies were similar to our study.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, measured data under various conditions were included in the data for development or evaluation of the current equations. Moreover, there is a report that although there were significant changes in body composition estimates after meals, these were small and within the imprecision of the impedance technique and so are unlikely to be of clinical significance [25]. Based on this report, we considered that the various intervals from meals to measurements might not have a significant impact on the results.…”
Section: Discussionmentioning
confidence: 97%